Research of the Anti-Fictional Characteristics in Persea (Avocado): A Review Study (International Journal of Innovative Research in Engineering & Management, 2021)
Natural products are being used towards pathogenic microbes  since the discovery of penicillin. However, there has been  increase in the frequency of microbes that are multi-antibiotic  resistant which demonstrates that novel antibiotics are now  much needed. Antibiotic resistance acts by changing the target  of antibiotics, by increasing the efflux of antibiotic & by  degrading the antibiotic itself. In this regard, this paper has  attempted to evaluate the antimicrobial property of the avocado  oil. Firstly, the oil was obtained commercially and the paper  discs were laced with increasing amounts of it & then kept on  a lawn culture of Candida albicans & Saccharomyces  cerevisiae. The results were observed for 24 hours  &Cyclohexamide was taken as positive control. After 24 hours,  Cyclohexamide showed highest zone of inhibition while the  increasing amount of the oil also showed good inhibition. This  thereby opens up the possibility of procuring anti-fungals or  even antibiotics from this oil commercially.
Keywords: Antibiotic Resistance; Avocado Oil; Candida Albicans; Cyclohexamide; Paper Disc Assay; Saccharomyces Cerevisiae; Zone of Inhibition